Complete chloroplast genome of Clematis fusca var. coreana (Ranunculaceae). (1st November 2016) - Park, Kyu Tae; Park, Seonjoo
Abstract: The complete chloroplast (cp) genome sequence of Clematis fusca var. coreana, an endemic plant in Korea, was determined. The genome size is 159, 609 bp in length, with 38% GC content. A pair of inverted repeats (IRs) of 31, 039 bp is separated by a large single copy (LSC) and a small single copy (SSC) of 79, 478 bp and 18, 053 bp, respectively. The complete cp genome contains 112 unique genes, including 79 coding genes, 4 rRNA genes, and 29 tRNA genes.